Analyzing the role of climatic factors on road accidents (Case study: Ardabil-Parsabad road in Ardabil Province, Iran) - Alizadeh, Sadegheh (Pure and Applied Science Advances, 2014)
Road accidents and their fatalities are among the currentchallenges human society facing, which in turn resulting in huge social and economiccosts on the countries. Thedeveloping countries are the biggest victims of the road accidents such that inthese countries, road accidents are considered asthe major cause of death. Unfortunately, Iran is amongthe countries in which the rate of road accidents is high. Among thedriving factors that affect road safety and transport isclimate. Ardabil-Parsabad road in Ardabil province is one of the roads manyaccidents have been occurred during years, and thistrend began when the number of cars increased resulted in huge road deaths in1990s. In this study, data has been used from four meteorological stations inArdabil, Samian, Meshkin-Shahr and Parsabad, over a period of5years(2008-2002).For this purpose, several climatic elements werecollected including the average daily temperature, average of minimum temperatures,average of maximum temperatures, the number of snowy days, the number of frostdays, starting glacial period, duration of the snowfall, duration of theglacial period, total average humidity and moderate precipitation, average of sunnyhours, average number of foggy days, the average number of windy days. This analysis is provided using Excel software inthe Arc GIS environment of continuous levels of these parameters in the region.